Intervensi Pengolahan Sampah Organik dengan Biopori serta Penyediaan Jamban Sehat Percontohan di Kelurahan Tabing Banda Gadang Kota Padang - Miladil Fitra; Sri Lestari Adriyanti; Irmawartini; Awaluddin; Basuki Ario Seno (CV. CENDIKIA JENIUS INDONESIA, 2025)
Geographically, Batipuh Panjang Village has an area of 14.32 km2 with a Community service activities aim to apply Science and Technology and improve knowledge and skills in the health sector, form/develop independent community groups in the field of environmental health and apply organic waste management with biopore tubes and build healthy latrines to improve community health in order to achieve prosperity. public. The implementation method used is the method of processing organic waste using the biopore method and making model latrines. The results of community service were the handing over of 25 biopori tubes to residents and the construction of a healthy latrine at Inu Hendra Yeni's house RT.05 RW.2, Tabing Banda Gadang Village. Conclusion: the community has implemented Biopori tubes in their homes and understands how to use Biopori and knows examples of healthy latrines.